Reduction system for cast casting small quantities of precious metals - Basilio Minaya, Hermes (2022)
In Peru, there are two types of jewelry practice (industrial and artisanal) the second mentioned has a greater participation of people in this context the contribution is for the development of artisanal jewelry (handmade) carrying out a variety of operations with a very high incidence in the manual elaboration to obtain the product (jewel) for sale in the national market. Within the processing: initial step is with casting, in this area the analysis and follow-up was carried out to obtain the optimal and adequate alloy, in this procedure the phenomenon of the oxidation of the material (alloy) occurs, whose manifestation is the affirmation in the superficial part of the visible material, due to the lack of the inert system (zone without oxygen) necessary in it, to reduce the event, the lack of oxygen containment, does not contribute to the good surface presentation after casting, ultimately influencing the preparation and the finish of the jewel, specifically in silver and gold, taking great care with these metals with the fulfillment of quality, attentive to the occurrence of good appearance, must present qualities such as cleanliness inside and on the surface, which will facilitate the presentation, for the following processes within the preparation of the jewel, especially with the brightness of the aforementioned precious metals, s requested in the pieces made. The artisan jeweler (micro, small or independent) have too many economic limitations for that reason they do not have a reduction system, with the present proposal it will benefit and it is directed to them; feasible and friendly to the environment, economically favorable due to the ease of application for jewelers, it is within the reach of operators and all those involved in this manufacturing specialty, taking into account the economic and labor reality of manufacturers, differing from those made industrially .